2021
DOI: 10.3389/fpsyt.2021.630247
|View full text |Cite
|
Sign up to set email alerts
|

The Behavioral Sequelae of Cannabis Use in Healthy People: A Systematic Review

Abstract: Background: Cannabis is known to have a broad range of effects on behavior, including experiencing a “high” and tranquility/relaxation. However, there are several adverse behavioral sequalae that can arise from cannabis use, depending on frequency of use, potency (e.g., THC content), age of onset, and cumulative exposure. This systematic review examined evidence for cannabis-related adverse behavioral sequalae in otherwise healthy human subjects.Methods: Following PRISMA guidelines, we conducted a systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 182 publications
(166 reference statements)
1
35
0
Order By: Relevance
“…Although most of the evidence on the cognitive sequelae of cannabis use has been provided by cross‐sectional data associated with methodological limitations, a growing number of longitudinal studies, which are useful to address causal inferences, have emerged. This has led to several reviews examining, among others, evidence provided by prospective designed studies [20, 27, 31, 81]. For instance, Bourque et al .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although most of the evidence on the cognitive sequelae of cannabis use has been provided by cross‐sectional data associated with methodological limitations, a growing number of longitudinal studies, which are useful to address causal inferences, have emerged. This has led to several reviews examining, among others, evidence provided by prospective designed studies [20, 27, 31, 81]. For instance, Bourque et al .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence pertaining to other domains, including attention and processing speed, led to more divergent findings. These reviews concluded that neurocognitive impairments may be dose‐dependent, particularly for domains related to memory [31], and effects may persist for at least 1 week when cannabis use is chronic, although these deficits are often resolved with long abstinence periods [26, 43]. Furthermore, Ganzer et al .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations